Evaluation of the implementation of a quality system in a basic research laboratory: viability and impacts - Hilda Carolina de Jesus Rios Fraga; Kiyoshi Ferreira Fukutani; Fabiana Santana Celes; Aldina Maria Prado Barral; Camila Indiani de Oliveira (Einstein (São Paulo))
OBJECTIVE: To evaluate the process of implementing a quality management system in a basic research laboratory of a public institution, particularly considering the feasibility and impacts of this improvement. METHODS: This was a prospective and qualitative study. We employed the norm "NIT DICLA 035 - Princípios das Boas Práticas de Laboratório (BPL)" and auxiliary documents of Organisation for Economic Co-operation and Development to complement the planning and implementation of a Quality System, in a basic research laboratory. In parallel, we used the PDCA tool to define the goals of each phase of the implementation process. RESULTS: This study enabled the laboratory to comply with the NIT DICLA 035 norm and to implement this norm during execution of a research study. Accordingly, documents were prepared and routines were established such as the registration of non-conformities, traceability of research data and equipment calibration. CONCLUSION: The implementation of a quality system, the setting of a laboratory focused on basic research is feasible once certain structural changes are made. Importantly, impacts were noticed during the process, which could be related to several improvements in the laboratory routine.